Effect of Gushen shetuo decoction in improving motor and non-motor symptoms and the expression of PERK, ATF4 and CHOP in patients with Parkinson's disease: Effects of Gushen shetuo decoction on Parkinson's disease - Li, Peishan; Yang, Ning; Guo, Weifeng; Ning, Houxu; Cheng, Wenhao; Wang, Haidong (Cellular and Molecular Biology, 2023)
This study aims to observe the therapeutic effect of Gushen Shetuo decoction on Parkinson's disease (PD), so as to provide reference for clinical practice. In order to demonstrate the clinical value of Gushen Shetuo Decoction, we selected 80 patients with PD for the study. Among them, 38 patients received the Gushen Shetuo decoction (research group), and 42 patients received Levodopa and Benserazide Hydrochloride Tablets (control group). There was no difference in Non-Motor Symptoms Scale (NMSS) scores between the research group and the control group (P>0. 05). However, the scores of motor complications in Movement Disorder Society-sponsored revision of the Parkinson's Disease Rating Scale (MDS-UPDRS) and those of Drooling Severity and Frequency Scale (DSFS) in the research group were lower than those in the control group (P<0. 05). Subsequently, we established PD model rats, and after Gushen Shetuo Decoction gavage treatment, we found that rats in the intervention group had increased mobility (P<0. 05), as well as notably improved pathological damage of substantia nigra and striatum. Also, the expression of PERK, ATF4 and CHOP in the brain tissues of rats in the intervention group was lower than those in the control group (P<0. 05). These results confirm that Gushen Shetuo decoction effectively improved the drooling of patients with PD and showed high safety.